1990
DOI: 10.1557/jmr.1990.1763
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the oxygen-related defect in aluminum nitride

Abstract: The oxygen-related defect in an aluminum nitride (A1N) single crystal and in polycrystalline ceramics is investigated utilizing photoluminescence spectroscopy, thermal conductivity measurements, x-ray diffraction lattice parameter measurements, and transmission electron microscopy. The results of these measurements indicate that at oxygen concentrations near 0.75 at. %, a transition in the oxygen accommodating defect occurs. On both sides of this transition, simple structural models for the oxygen defect are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
86
0
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(123 citation statements)
references
References 31 publications
16
86
0
10
Order By: Relevance
“…PL caused by intrinsic defects such as vacancies, O impurities, and their complexes in AlN is well known. [22][23][24][25] AlN is extremely susceptible to O contamination, so O impurities are typically considered intrinsic. Studies on AlN ceramics 22,23 observed a PL peak in the ∼300 to 375 nm region and attributed it to an O related defect complex [V A1 -O N · ].…”
Section: -5mentioning
confidence: 99%
“…PL caused by intrinsic defects such as vacancies, O impurities, and their complexes in AlN is well known. [22][23][24][25] AlN is extremely susceptible to O contamination, so O impurities are typically considered intrinsic. Studies on AlN ceramics 22,23 observed a PL peak in the ∼300 to 375 nm region and attributed it to an O related defect complex [V A1 -O N · ].…”
Section: -5mentioning
confidence: 99%
“…The thermal conductivity of AlN ceramics is greatly affected by the presence of metallic impurities [38], and oxygen impurity [39][40][41] present on the surface of the starting AlN powder in the form of Al 2 O 3 due to spontaneous reaction with air, and also dissolved in the AlN lattice. The lattice distortion due to aluminium vacancies resulting from incorporation of oxygen into the lattice leads to increased phonon scattering, thus lowering the thermal conductivity of the material [25,[42][43][44][45][46].…”
Section: Aluminium Nitridementioning
confidence: 99%
“…At room temperature, oxygen-related defects are the dominant mechanism limiting the thermal conductivity of AlN [22,40], but their effect decreases at elevated temperatures [24]. Metallic impurities also have the effect of greatly reducing the RT thermal conductivity [38].…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…11,12 Oxygen adversely affects the properties, crystal quality, and surface morphology of the AlN crystals. [13][14][15][16] At low concentrations, oxygen promotes the formation of Al vacancies which significantly reduces AlN's thermal conductivity. 13 With increasing oxygen concentration and hence Al vacancy concentrations, the Al vacancies coalesce, forming stacking faults, inversion domains, and more extended defects.…”
Section: 10mentioning
confidence: 99%